Enhancement of cognitive function in mice with Alzheimer’s disease through hyperbaric oxygen-induced activation of cellular autophagy - Fan, Qian-Qian; Chen, Yong-Min; Fu, Yong-Sen; Li, Xiao-Shan; Zeng, Ji; Bian, Shao-Zhen; Li, Bin-Bin; Song, Zhen-Hua (Frontiers in Aging Neuroscience, 2024)
Objective In this study, we examined the effectiveness of hyperbaric oxygen (HBO) therapy in ameliorating cognitive deficits in mice with Alzheimer’s disease (AD), while also assessing its impact on the autophagic pathway within the context of AD. Methods 20 double-transgenic mice expressing the amyloid precursor protein and presenilin 1 (APP/PS1) were purposefully selected and randomly assigned to groups A and B. Concurrently, 20 C57BL/6 mice were chosen and randomly categorized into groups C and D, each consisting of 10 mice. Mice in groups B and D received HBO treatment. The Morris water maze assay was used to assess changes in mouse behavior. Immunohistochemistry techniques were used to quantify the expression levels of amyloid-beta 42 (Aβ42) and microtubule-associated protein 1A/1B-light chain 3 (LC3) in hippocampal tissues, while western blot analysis was used to investigate the levels of LC3-II, p62, phosphoinositide 3-kinase (PI3K), and mammalian target of rapamycin (mTOR) proteins within hippocampal tissues. Results Mice allocated to group B exhibited reduced escape latency and prolonged dwell time in the target quadrant compared to other groups. Histological examination revealed conspicuous plaque-like deposits of Aβ42 in the hippocampal tissues of mice in groups A and B. Group B displayed diminished Aβ42-positive reactants and augmented microtubule-associated protein 1A/1B-LC3-positive reactants compared to group A. LC3-positive reactants were also detected in the hippocampal tissues of mice in groups C and D, surpassing the levels observed in groups A and B. Furthermore, group B demonstrated significantly lower expression of mTOR protein and markedly higher expression of LC3-II protein in mouse hippocampal tissues when compared to group A (P < 0.05). Conversely, there were no significant disparities noted in PI3K and p62 protein expression between groups B and A. Notably, no discernible discrepancies were observed in the expression levels of mTOR, PI3K, LC3-II, and p62 proteins between groups C and D within mouse hippocampal tissues. Conclusion HBO treatment demonstrates efficacy in enhancing cognitive function in mice with AD and holds promise as a potential therapeutic intervention for AD by facilitating the activation of the mTOR pathway-mediated autophagy.